Efficient algal lipid extraction via photocatalysis and its conversion to biofuel. (15th April 2016) - Shwetharani, R.; Balakrishna, R. Geetha
Graphical abstract: Nanostructured semiconductor materials were used for photocatalytic algal cell membrane destruction leading to renewable algal oil production. Highlights: We report an efficient photocatalytic process for algal cell disruption leading to lipid release and thereby fuel generation. The method eradicates dewatering and drying steps required for conventional sustainable algal fuel production. This technique being economical, yields 52% of algal oil, on par with the existing pilot scale techniques. Abstract: Microalgae play an important role in energy production to solve the major energy crisis. The present study demonstrates an efficient and environmental friendly route for bio-oil extraction from wet Nannochloropsis oculata algal biomass through photocatalysis. The method uses abundant solar energy and catalytic amount of titanium dioxide photocatalyst for the rupturing of wet algal cells and reduces most of the cost by avoiding dewatering and drying, for algal oil production. The various spectroscopy and microscopy techniques used show destruction of algal cell membrane by the photocatalyst, with a release of 52.2% lipid yield. The obtained lipid by photocatalysis on esterification yields biofuel which is in complete agreement with results obtained from conventional techniques. Algal oil is converted to biofuel through acid catalyzed transesterification. Bio-oil and biofuel samples were analyzed by ATR-IR, NMR and GCMS. The physicochemical characterization of photocatalyst was carried out by UV–Visible spectroscopy, XRD, EDS, BET and electron microscopy studies. The results suggest that the nanoparticles are efficient catalysts for rupturing the rigid micro algal cell membrane in an aqueous environment, using sunlight and hence prove to be a potential economic method for large scale bio-oil extraction.